Nutrition policy in West Africa - Vanderkooy, A.; Verstraeten, Roosmarijn; Diatta, Ampa Dogui; Diop, Loty; Touré, Mariama (International Food Policy Research Institute, 2019)
This brief summarizes nutrition-relevant policies, strategies, and action plans (all referred to as ‘policies’ in this brief) in West Africa. With a focus on the six nutrition challenges that make up the World Health Assembly (WHA) global targets, we examine i) nutrition context, policy objectives, indicators, budget, and activities, ii) key beneficiaries, actors and coordination, iii) monitoring, evaluation, and accountability, and iv) the extent to which current policies are aligned with the WHA targets.